Leptin Enhances Nitric Oxide Production and Decreases Blood Flow in Rat Skeletal Muscle - Savaş Üstünova; Ayşegül Kapucu; Cihan Demirci Tansel (European Journal of Biology)
Objective: There are a few studies related to nitric oxide (NO) and leptin interaction in the regulation of physiological events in skeletal muscle. Therefore, the aim of the present study is to investigate the interaction of leptin and NO in response to blood flow and nitric oxide synthase (NOS) distribution on rat skeletal muscle. Materials and Methods: Twenty-four adult-male Wistar albino rats were divided into 4 groups: control (C), Leptin (LP) (50 μg/kg), L-NG-nitroarginine methyl ester (LN) (a non-specific nitric oxide synthase inhibitor, 10 mg/kg,) and L-NAME+Leptin (LN+LP) administrated groups. Drugs were administered via the right jugular vein. Hemodynamic parameters: mean arterial pressure, heart rate and blood flow were recorded during the experiment and at the end blood samples for biochemical analyses of leptin and nitrite/nitrate levels and gastrocnemius muscle tissues from the right hindlimb for NOS distribution were taken. Results: Leptin infusion after L-NAME administration significantly decreased heart rate and blood flow (p<0.05, p<0.001). In addition, there was no change in the mean arterial pressure in the leptin group and leptin-administered L-NAME group. Leptin levels were the highest in the LP+LN group (p<0.01). Decreased nitrate/nitrate levels with L-NAME administration (p<0.01 vs C) reached control values by leptin infusion. Both endothelial NOS (eNOS) and neuronal NOS (nNOS) distributions were observed in the skeletal muscle cells of the leptin group. Conclusion: Although NO synthesis is inhibited by L-NAME, it is concluded that leptin partially enhances NO production and leptin uses NO as a mediator in its physiological effects.